Cytokine Panels and Pediatric Acute Respiratory Distress Syndrome: A Translational Investigation*. Issue 12 (December 2020) - McKeone, Daniel J.; Mathewson, Margaret; Dalal, Priti G.; Spear, Debbie; Umstead, Todd M.; Hicks, Steven D.; Chroneos, Zissis C.; Wang, Ming; Thomas, Neal J.; Halstead, E. Scott
Abstract : Objectives: To identify and compare serum and lower respiratory tract fluid biomarkers of lung injury using well-characterized mouse models of lung injury. To explore the relationship between these preclinical biomarkers and clinical outcomes in a discovery cohort of pediatric patients with acute respiratory failure from pneumonia. Design: Prospective, observational cohort study. Setting: A basic science laboratory and the PICU of a tertiary-care children's hospital. Patients: PICU patients intubated for respiratory failure from a suspected respiratory infection. Interventions: Prospective enrollment and collection of lower respiratory tract fluid samples. Measurements and Main Results: C57BL6/J mice were intranasally inoculated with escalating doses of influenza A virus or toll-like receptor agonists to simulate varying degrees of lung injury. Serum and bronchoalveolar lavage fluid were measured for the presence of cytokines using commercially available multiplex cytokine assays. Elevated levels of C-C motif chemokine ligand 7 at the peak of inflammation in both bronchoalveolar lavage fluid and serum correlated with lethality, with the bronchoalveolar lavage fluid ratio of C-C motif chemokine ligand 7:C-C motif chemokine ligand 22 providing the best prediction in the mouse models. These preclinical biomarkers were examined in the plasma and lower respiratory tract fluid of a discovery cohort of pediatric patients with acute respiratory failure from pneumonia. The primary clinical outcome measure was ventilator-free days, with secondary outcomes of pediatric acute respiratory distress syndrome severity and mortality. Elevation in peak lower respiratory tract fluid C-C motif chemokine ligand 7:C-C motif chemokine ligand 22 ratios demonstrated a significant negative correlation with ventilator-free days ( r = –0.805; p < 0.02). Conclusions: This study provides evidence that lung immune profiling via lower respiratory tract fluid cytokine analysis is feasible and may provide insight into clinical outcomes. Further validation of markers, including the C-C motif chemokine ligand 7:C-C motif chemokine ligand 22 ratio in this limited study, in a larger cohort of patients is necessary. Abstract : Supplemental Digital Content is available in the text.